Service robots in organisational frontlines-A retail managers' perspective - Meyer, Patrick; Roth, Angela; Gutknecht, Klaus (Journal of Retailing and Consumer Services, 2023)
Service robots (SR) have the potential to revitalise value creation in brick-and-mortar retailing. While both the competitive and evolving nature of the retailing industry as well as customers and FLE have obtained substantial coverage in academic literature, the managerial angle towards SR in organisational frontlines has rarely been addressed in service research. This qualitative exploratory interview study explores retail managers' perceptions of SR in organisational frontlines. Building on 28 in-depth interviews with retail managers, three dimensions of predisposing factors (impact on the functional, relational and organisational level), as well as two aggregated dimensions of managerial coping strategies (transforming FLE and work routines) were identified. Further, the findings reveal that retail managers perceive inherent difficulties in balancing the needs of customers and FLE when it comes to effective SR implementation.
Created from Fastlane, WoS look-up